Performance analysis for an inclined tubular still desalination integrated with evacuated tube collector. (August 2021) - Essa, Mohamed A.; Eewayed, Estabrak N.; Gobran, Mohamed H.; Mostafa, Nabil H.
Highlights: The smallest water film thickness in the ETC achieves the largest freshwater productivity. The large size condenser achieves the largest freshwater productivity of 4.5 l/m 2 ·day. The same condenser and Collector's inclination achieves maximum productivity. The vapor leakage increases with decreasing the condenser's size. Discovering a novel nature of operation for such systems according to the asynchronous evaporation and desalination rates. The productivity is cyclic according to the environmental conditions variation. Abstract: Energy efficiency is one of the major challenges in water desalination systems. In the present study, a novel improvement for the Evacuated tube collector as a vapor generator was proposed. This improvement is achieved by decreasing the heat capacity using a film of feed water beside the absorber tube. The proposed system operated in continuous feedwater flow with backup. An inclined tubular still was used for vapor condensation. The inclination angle of the still and its diameter were investigated. The study was performed experimentally with a theoretical analysis of the thermal energy conversion. Water film thicknesses (WFT) of 2, 4, and 6 mm were examined. The 2 mm WFT achieved the optimum overall efficiency of 53%. The tested diameters of the tubular still were 80, 120, and 160 mm. The 160 mm diameter achieved the highest overall efficiency of 60.2%. Moreover, the 160 mm diameter condenser achieved the best vapor storage option. The tested inclination angles of the still were 80°, 62°, and 45°. The 45° angle achieved the best overall efficiency of 48.1%. The cost of the distilled water reaches 0.01205 /L per unit collector area.